2020
DOI: 10.3390/healthcare8040479
|View full text |Cite
|
Sign up to set email alerts
|

High Visceral Fat Area Attenuated the Negative Association between High Body Mass Index and Sarcopenia in Community-Dwelling Older Chinese People

Abstract: The association between obesity and sarcopenia remains controversial. The present study was conducted to explore the associations among body mass index (BMI), visceral fat area (VFA), and sarcopenia in older people and analyze their potential mechanisms. This cross-sectional study included 861 community-dwelling older Chinese people from three regions of China. BMI, VFA, muscle mass, muscle strength, physical performance, body composition, and metabolic markers were measured. Muscle mass and muscle strength we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…In relation to the effects of resistance training on BFM, sarcopenia often is associated with obesity due to changes in endocrine function and a lack of physical activity leading to reduced muscle mass and strength. Older people with sarcopenia tend to show high levels of body fat and visceral fat [ 52 ]. When sarcopenia is combined with obesity, it is called sarcopenic obesity (SO).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the effects of resistance training on BFM, sarcopenia often is associated with obesity due to changes in endocrine function and a lack of physical activity leading to reduced muscle mass and strength. Older people with sarcopenia tend to show high levels of body fat and visceral fat [ 52 ]. When sarcopenia is combined with obesity, it is called sarcopenic obesity (SO).…”
Section: Discussionmentioning
confidence: 99%
“…A combination of reduced lean body mass and increased visceral fat is also associated with decreased physical function, increased risk of disability, worsening hospitalization, increased morbidity, and premature mortality [27]. An increase in visceral fat can lead to systemic inflammation and insulin resistance, which can in turn lead to low muscle mass and sarcopenia in the elderly [28]. In addition, decreased movement due to loss of skeletal muscle function accelerates muscle fat infiltration, which is closely related to physical inactivity [29].…”
Section: Table 3 Logistic Regression Analysis Of Obesity Defined By B...mentioning
confidence: 99%
“…A Japanese study found elderly diabetes patients with low BMI and high body fat mass may be more likely to develop sarcopenia ( 17 ). Without taking body fat into account, subjects with high BMI tend to have more lean body mass ( 18 , 19 ). Therefore, BMI might reflect lean mass in elderly diabetes patients ( 17 ).…”
Section: Discussionmentioning
confidence: 99%